Recent Advances Inspection Technologies In Food Safety Health Hazards For Fish and Fish Products - Peiru Gao; Sharifudin Md Shaarani; Nor Qhairul Izzreen Mohd Noor (Informa UK Limited, 2024)
Indexed by Scopus/ERA